BBPPMP Public Relations Strategy in Enhancing Institutional Image Through the Development Program of Sukaresmi Village - Jamil Ridho; Suparman (Yayasan Sinergi Kawula Muda, 2026)
This study examines the Public Relations strategy of the Center for Agricultural Modernization Development and Application (BBPPMP) in strengthening institutional image through the development program in Sukaresmi Village. The research is grounded in the Strategic Digital Public Relations (SDPR) theory, which emphasizes technology-based communication, data-driven decision-making, and two-way digital engagement. Using a qualitative descriptive method, data were collected through observation, interviews, participation, and literature review to explore the communication processes implemented throughout the program. The findings show that BBPPMP successfully applied the three pillars of SDPR by integrating digital media for program dissemination, utilizing field data to design communication strategies, and fostering dialogic engagement with village stakeholders and local MSME actors. These efforts contributed to improving community understanding, participation, and perception of the institution. However, challenges emerged, including low digital literacy, limited technological infrastructure, and varying levels of community readiness in adopting digital-based communication. Despite these obstacles, the overall implementation of the PR strategy proved effective in supporting institutional image-building and strengthening collaborative relationships with the community.